Acute air pollution and temperature exposure as independent and joint triggers of spontaneous preterm birth in New South Wales, Australia: a time-to-event analysis - Tanya Singh; Tanya Singh; Bin Jalaludin; Bin Jalaludin; Shakoor Hajat; Geoffrey G. Morgan; Geoffrey G. Morgan; Geoffrey G. Morgan; Geoffrey G. Morgan; Katrin Meissner; Katrin Meissner; John Kaldor; et al. (Frontiers Media S.A., 2023)
IntroductionExposure to high ambient temperatures and air pollution has been shown to increase the risk of spontaneous preterm birth (sPTB). Less clear are the effects of cold and the joint effects of air pollution and temperature.MethodsUsing a Cox proportional hazard regression model, we assessed the risk of independent and combined short-term exposure to ambient daily mean temperature and PM2.5 associated with sPTB in the last week before delivery on overall sPTB (weeks 23-36) and three subtypes: extremely sPTB, very sPTB, and moderate-to-late sPTB for a birth cohort of 1,318,570 births from Australia (Jan 2001-Dec 2019), while controlling for chronic exposure (i.e., throughout pregnancy except the last week before delivery) to PM2.5 and temperature. The temperature was modeled as a natural cubic spline, PM2.5 as a linear term, and the interaction effect was estimated using a multiplicative term. For short-term exposure to temperature hazard ratios reported are relative to the median temperature (18.1°C).ResultsHazard ratios at low temperature [5th percentile(11.5°C)] were 0.95 (95% CI: 0.90, 1.00), 1.08 (95% CI: 0.84, 1.4), 0.87 (95% CI: 0.71, 1.06), and 1.00 (95% CI: 0.94, 1.06) and greater for high temperature [95th percentile (24.5°C)]: 1.22 (95% CI: 1.16, 1.28), 1.27 (95% CI: 1.03, 1.57), and 1.26 (95% CI: 1.05, 1.5) and 1.05 (1.00, 1.11), respectively, for overall, extremely, very, and moderate-to-late sPTBs. While chronic exposure to PM2.5 had adverse effects on sPTB, short-term exposure to PM2.5 appeared to have a negative association with all types of sPTB, with hazard ratios ranging from 0.86 (95th CI: 0.80, 0.94) to 0.98 (95th CI: 0.97, 1.00) per 5 μg/m3 increase in PM2.5.DiscussionThe risk of sPTB was found to increase following acute exposure to hot and cold ambient temperatures. Earlier sPTB subtypes seemed to be the most vulnerable. This study adds to the evidence that short-term exposure to ambient cold and heat and longer term gestational exposure to ambient PM2.5 are associated with an elevated risk of sPTB.